IoT-based Wind Speed Measurement System - Alif Yulanda Putri; - Yulkifli; - Syafriani; Yenni Darvina (PILLAR OF PHYSICS, 2023)
Weather is the state of the atmosphere at any time which is expressed by the high and low values of the weather element parameters. Observations of weather elements are carried out so that they can be used as needed in the future. This study aims to determine the performance and design specifications of a wind speed measurement system based on the internet of things with a smartphone display. This measuring instrument is built using a wind speed sensor, namely a wind speed sensor as a speed sensor, Arduino Uno to connect sensor readings to NodeMCU, the NodeMCU ESP8266 microcontroller which is used to access the internet network so that it can be sent to the thingspeak server and data from thingspeak is displayed on an android smartphone using inventory application. The results of measuring, testing, and analyzing wind speed using the Internet of Things and a smartphone display, namely Arduino Uno, process the wind speed detected by the wind speed sensor before sending it to NodeMCU ESP8266. After that, the data is sent to the thingspeak server which will be displayed on the Android phone. Second, the average accuracy of wind speed measurements on the first, second, and third days were 95.96%, 94.83%, 96.16%, and the average accuracy of wind speed measurements on the first, second, and third days were 92.85%, 94.43% and 96%.